2020
DOI: 10.3389/fvets.2020.612130
|View full text |Cite|
|
Sign up to set email alerts
|

The Expression of Proteins Related to Serotonin Pathway in Pulmonary Arteries of Dogs Affected With Pulmonary Hypertension Secondary to Degenerative Mitral Valve Disease

Abstract: Background: Pulmonary hypertension (PH) can cause medial thickening, a hallmark of pulmonary arterial remodeling. The serotonin (5HT) pathway has been suggested as a factor associated with PH by inducing pulmonary arterial smooth muscle cells (SMCs) proliferation, a major cause of medial thickening. This study aims to demonstrate the expression of molecules in the 5HT pathway in the pulmonary artery of dogs affected with PH secondary to degenerative mitral valve disease (DMVD) compared to DMVD and healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
(116 reference statements)
2
11
0
Order By: Relevance
“…The studies in laboratory animals have shown that 5-HT stimulated vasoconstriction and remodeling by causing contraction, proliferation and differentiation of PASMC [ 27 , 28 , 29 ]. The medial thickening associated with the expression of proteins related to the 5-HT signaling of PA was highlighted in a previous immunohistochemical study of PA in dogs with DMVD and dogs with PH due to DMVD [ 33 ]. Similarly, the present study found that the relative expression of some proteins, TPH-1 and 5-HTR2A, tended to be upregulated in the PA tissues of dogs in the DMVD and DMVD with PH groups, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies in laboratory animals have shown that 5-HT stimulated vasoconstriction and remodeling by causing contraction, proliferation and differentiation of PASMC [ 27 , 28 , 29 ]. The medial thickening associated with the expression of proteins related to the 5-HT signaling of PA was highlighted in a previous immunohistochemical study of PA in dogs with DMVD and dogs with PH due to DMVD [ 33 ]. Similarly, the present study found that the relative expression of some proteins, TPH-1 and 5-HTR2A, tended to be upregulated in the PA tissues of dogs in the DMVD and DMVD with PH groups, although this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT is transported via the PAECs and PASMCs through the mediation of SERT [ 18 , 54 ]. In a previous immunohistochemical study of dogs with PH due to DMVD, SERT was expressed mainly in PASMCs, and upregulation of SERT was detected in dogs affected with DMVD with and without PH compared with normal dogs [ 33 ]. In lung tissue, the immunohistochemical study showed that SERT was expressed by pneumocytes and PAMs, similar to an investigation in rat models [ 49 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is then transferred to pulmonary artery smooth muscle cells via SERT and serotonin receptors to mediate the downstream effectors in the serotonin signaling pathway, causing contraction, proliferation and differentiation of pulmonary arterial walls (17)(18)(19)(20). Pulmonary arterial wall thickening has been found with overexpression of proteins related to the serotonin signaling pathway, including TPH-1, SERT, serotonin receptor 2A, extracellular signal-regulated kinase 1/2 (ERK1/2) and phosphorylated ERK1/2 (pERK1/2) in dogs with PH secondary to DMVD (21). However, the association of circulating serotonin and PH secondary to DMVD in dogs has not been studied.…”
Section: Introductionmentioning
confidence: 99%